Konstruksi dan Resistensi Beban Ganda Kaluna dalam Film Home Sweet Loan Berdasarkan Performativitas Judith Butler - Devi Nadhifah; Luna Wahyu Anjani; Thirdian Naufalia Honest (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study analyzes the process of construction and resistance to the double burden experienced by the character Kaluna in the film Home Sweet Loan (2024) through the perspective of Judith Butler's gender performativity. Using qualitative content analysis on 13 key scenes, it was found that Kaluna's double burden of office work and bearing the economic and domestic responsibilities of an extended family was constructed through stylized repetition of acts. The results show that Kaluna experiences a double burden of professional and domestic work shaped by social norms and family expectations. However, the film also depicts Kaluna's resistance to this construction through verbal and emotional actions and personal decisions that challenge the patriarchal structure. This study concludes that Home Sweet Loan not only represents the double burden of modern women, but also shows women's agency in resisting and negotiating their gender identity. These actions deconstruct oppressive gender identities and form a new, independent subjectivity. The film emphasizes that the double burden of women is not a natural law, but rather a social performance that can be resisted.